2022
DOI: 10.1038/s41598-022-08618-x
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral administration of the antisecretory peptide AF16 cures murine gliomas and modulates macrophage functions

Abstract: Glioblastoma has remained the deadliest primary brain tumor while its current therapy offers only modest survival prolongation. Immunotherapy has failed to record notable benefits in routine glioblastoma treatment. Conventionally, immunotherapy relies on T cells as tumor-killing agents; however, T cells are outnumbered by macrophages in glioblastoma microenvironment. In this study, we explore the effect of AF16, a peptide from the endogenous antisecretory factor protein, on the survival of glioma-bearing mice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“… 60 A recent study explored the effect of treatment with the active peptide of AF, AF-16, in glioma-bearing mice, human and murine cells and demonstrated prolonged survival, decreased tumour size, changes in macrophage and T-cells invasion, and increased pro-inflammatory markers. 61 They found modulation of several inflammatory markers, for example, IL-8, MCP2, TNFSF14, by AF-16, 61 which may strengthen the associations demonstrated in the present study with a suggested role of AF in regulation of inflammatory processes. However, the mechanisms of positive or inverse associations need to be further studied.…”
Section: Discussionsupporting
confidence: 84%
“… 60 A recent study explored the effect of treatment with the active peptide of AF, AF-16, in glioma-bearing mice, human and murine cells and demonstrated prolonged survival, decreased tumour size, changes in macrophage and T-cells invasion, and increased pro-inflammatory markers. 61 They found modulation of several inflammatory markers, for example, IL-8, MCP2, TNFSF14, by AF-16, 61 which may strengthen the associations demonstrated in the present study with a suggested role of AF in regulation of inflammatory processes. However, the mechanisms of positive or inverse associations need to be further studied.…”
Section: Discussionsupporting
confidence: 84%
“…Also, it has been proposed that AF may be involved in the complement cascade of the innate immune system [ 38 ]. Most recently, a study of AF16, an active peptide from the AF protein, showed that AF16 increased the secretion of typically proinflammatory cytokines from human and mouse M0 macrophages, and that intratumoral co-administration of TMZ and AF16 resulted in synergistically increased survival in glioma-bearing mice [ 26 ]. Taken together, the antisecretory and immunomodulatory mechanisms exerted by AF may contribute to suppressing tumor progression by reducing tumor-promoting inflammation and lowering tumoral IFP, as well as giving symptomatic relief by reducing brain edema.…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that SPC-flakes combined with TMZ successfully prevented tumor growth and increased overall survival at 120 days from 30 to 100% compared to TMZ monotherapy [ 25 ]. Our own results show that intratumoral delivery of an active AF peptide, AF-16, boosts the effect of intratumoral chemotherapy and immune reactivity in an experimental glioma model [ 26 ].…”
Section: Introductionmentioning
confidence: 99%